2022
DOI: 10.1111/ans.17751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perioperative fluid volume restriction on the incidence of complications following pancreaticoduodenectomy

Abstract: Background: Perioperative fluid restriction has been suggested to reduce morbidity and length of stay. The purpose of this study was to compare the morbidity following pancreaticoduodenectomy (PD) between fluid restriction group and conventional management group. Methods: Seventy-two patients were enrolled for perioperative fluid restriction of PD. During the operation, main fluid was infused at a rate of less than 8 mL/kg/hr. Until POD#3, 10% dextrose and Hartmann's solution were administered at rates of 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…While there is conflicting evidence, some trials have demonstrated benefits and reduced postoperative complications and length of stay in patients with restrictive fluid regimens [ 13 , 15 , 31 ]. Other studies, consistent with our data, have failed to reproduce these benefits [ 9 , 12 , 29 , 32 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While there is conflicting evidence, some trials have demonstrated benefits and reduced postoperative complications and length of stay in patients with restrictive fluid regimens [ 13 , 15 , 31 ]. Other studies, consistent with our data, have failed to reproduce these benefits [ 9 , 12 , 29 , 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…In those studies, increased intraoperative [ 9 ] or post-operative [ 15 ] fluid balance was associated with a CR-POPF. Others showed no multivariate association between volume status and Grade B or C POPF [ 6 , 11 , 12 , 37 ]. Our multivariate observations align with the findings that indicate no association between volume status and Grade B or C POPF.…”
Section: Discussionmentioning
confidence: 99%
“…[13,15,32] Other studies, consistent with our data, have failed to reproduce these bene ts. [9,12,30,33] Large-scale studies of noncardiac surgeries have shown a positive association between low blood pressure and AKI and other adverse clinical outcomes. [2,23,34] There has been limited investigation of the impact of low blood pressure in pancreatic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Intraoperative improvements in uid and blood pressure management may further reduce the overall rate of postoperative complications, including pancreatic stula and Clavien-Dindo complications. [9][10][11][12][13][14][15] Implementing enhanced recovery pathways for pancreatic surgery incorporates many evidence-based activities that have improved clinical outcomes and reduced costs.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have recommended restrictive fluid replacement to avoid potential risk factors in the perioperative period, reduce postoperative complications, and improve prognosis. 14 , 15 Fluid loss can be induced by primary diseases, anesthesia, surgery, and bleeding. The volume of fluid infusion and the types of electrolytes replaced by infusion should be respectively matched with the volume and electrolyte composition of the fluid lost.…”
Section: Discussionmentioning
confidence: 99%